Shifting focus from resistance to disease tolerance: A review on hybrid house mice. Issue 5 (7th May 2022) - Balard, Alice; Heitlinger, Emanuel
Abstract: Parasites have been proposed to modulate the fitness of hybridizing hosts in part based on observations in the European house mouse hybrid zone (HMHZ), a tension zone in which hybrids show reduced fitness. We here review evidence (1) for parasite load differences in hybrid versus parental mice and (2) for health and fitness effects of parasites promoting or preventing introgression and hybridization. The question of relative resistance or susceptibility of hybrids to parasites in the HMHZ has long been controversial. Recent field studies found hybrids to be more resistant than mice from parental subspecies against infections with pinworms and protozoans ( Eimeria spp.). We argue that the field studies underlying the contradictory impression of hybrid susceptibility have limitations in sample size, statistical analysis and scope, focusing only on macroparasites. We suggest that weighted evidence from field studies indicate hybrid resistance. Health is a fitness component through which resistance can modulate overall fitness. Resistance, however, should not be extrapolated directly to a fitness effect, as the relationship between resistance and health can be modulated by tolerance. In our own recent work, we found that the relationship between health and resistance (tolerance) differs between infections with the related species E .  falciformis and E .  ferrisi . Health and tolerance need to be assessed directly and the choice of parasite has made this difficult in previous experimental studies of house mice. We discuss how experimental Eimeria spp. infections in hybrid house mice can address resistance, health and tolerance in conjunction. Abstract : Our review shows evidence for hybrid vigor against in the house mouse hybrid zone. This vigor manifests in elevated resistance. We discuss that resistance is not necessarily a linked with fitness and argue that this research should switch its focus to tolerance. We describe house mice and protozoan parasites of the genus Eimeria as a host–parasite system in which this is possible.